Utilization of Student Podcast Media to Improve Listening and Text Composing Skills Dialogue in Mis Al Hidayah - Risky Erillia (Institut Agama Islam Negeri Palopo, 2025)
This study aims to describe the use of podcast media in improving listening skills and composing dialogue texts in fifth grade students at MIS Al Hidayah. This research uses a descriptive qualitative approach with a case study approach that seeks to explore how students utilize podcasts to hone their listening and dialogue building skills. The research was conducted in Mis Al Hidayah. The research subjects were fifth grade students at Mis Al Hidayah which has 25 students. The data collection techniques used were observation and interviews. Data analysis used was reduction, presentation, and verification. Based on the research results, it is known that the effective use of podcast media can improve students' listening skills in learning Indonesian. Through the activity of listening to audio conversations, students become more skilled at understanding the content of dialogue, capturing intonation and language expressions, and recognizing interaction patterns contained in a dialogue text. Podcasts provide a more contextual and engaging learning experience than conventional methods, making it easier for students to understand the material naturally.